The efficacy and safety of quinagolide in hyperprolactinemia treatment: A systematic review and meta-analysis - Zeng, Yanyang; Huang, Qingliang; Zou, Yunzhi; Tan, Jiacong; Zhou, Wu; Li, Meihua (Frontiers in Endocrinology, 2023)
Abstract Purpose Three dopamine agonists (bromocriptine, cabergoline and quinagolide) have been used for hyperprolactinemia treatment for decades. Several studies have reviewed the efficacy and safety of bromocriptine and cabergoline. However, no systematic review or meta-analysis has discussed the efficacy and safety of CV in hyperprolactinemia and prolactinoma treatment. Methods Five medical databases (PubMed, Web of Science, EMBASE, Scopus and the Cochrane Library) were searched up to May 9, 2022, to identify studies related to quinagolide and hyperprolactinemia. A meta-analysis was implemented by using a forest plot, funnel plot, sensitivity analysis, meta-regression and Egger test via software R 4.0 and STATA 12. Results A total of 1,211 studies were retrieved from the five medical databases, and 33 studies consisting of 827 patients were finally included in the analysis. The pooled proportions of patients with prolactin concentration normalization and tumor reduction (>50%) under quinagolide treatment were 69% and 20%, respectively, with 95% confidential intervals of 61-76% and 15-28%, respectively. The pooled proportion of adverse effects was 13%, with a 95% confidential interval of 11-16%. Conclusion Our study showed that quinagolide is not less effective than cabergoline and bromocriptine in treating hyperprolactinemia, and the side effects were not significant. Hence, this drug could be considered an alternative first-line or rescue treatment in treating hyperprolactinemia in the future.